Developmental Considerations in Obsessive Compulsive Disorder: Comparing Pediatric and Adult-Onset Cases - Geller, Daniel A.; Homayoun, Saffron; Johnson, Gabrielle (Frontiers in Psychiatry, 2021)
There appear to be two peaks of incidence of Obsessive Compulsive Disorder (OCD), one with a pre-adolescent onset and another in early adulthood. As new cases are added, the cumulative prevalence of OCD increases, but the great majority of cases have an onset in youth. The notion that early onset OCD represents a unique developmental subtype of the disorder has been considered by many researchers based on several specific age-related factors. Ascertainment and early intervention in affected youth is critical to abbreviate the functional impairments associated with untreated illness. In this paper we review the clinical, familial and translational biomarker correlates seen in early onset OCD that support the notion of a developmental subtype and discuss implications for research and treatment aimed at this cohort. The importance of cognitive, academic and social development tasks of childhood and adolescence, illness-specific and familial factors, and immune-mediated inflammatory factors are discussed, with their implications for management.